Bagasse Yield and Quality Traits of Silage Made From Juice-Extracted Sweet Sorghum (Sorghum bicolorvar saccharatum (L.) Mohlenbr.) Stalks . - Yucel, Celal; Bilgin, Feyza Dondu; Inal, Ilker; Hatipogl, Rustu (United Arab Emirates Univ, 2023)
This study was conducted to investigate possible use of juice-extracted sweet sorghum stalks (bagasse) as a quality roughage source through silage making. A total of 21 different sweet sorghum (Sorghum bicolor var. saccharatum (L.) Mohlenbr.) genotypes supplied from different sources were used as the primary material of the study. Field experiments were conducted in a randomized blocks design with 4 replications on the experimental fields of Eastern Mediterranean Agricultural Research Institute under 2nd crop conditions during the growing seasons of 2016 and 2017 years. Plants were harvested for bioethanol production at milk-dough stage of panicle grains. Plant leaves and panicles were stripped and remaining stalks were extracted through squeezing. Juice-extracted stalks (bagasse) were ensilaged for 60 days and quality traits were analyzed at the end of silage period. As the average of two years, bagasse yields varied between 42.6-113.9 t ha-1, silage DM yields varied between 11.6-40.0 t ha-1. In addition, crude protein (CP) content, acid detergent lignin (ADL), neutral detergent fiber (NDF) and acid detergent fiber (ADF) values varied between 29.79 -50.84 g/kg DM, between 49.3 -91.4 g/kg DM, between 525.1-694.8 g/kg DM and between 351.2-486.8 g/kg DM, respectively. It was concluded based on present findings that silages made from juice-extracted stalks of sweet sorghum grown under 2nd crop conditions of Cukurova region could be used as quality roughage source for livestock.
Keywords: Bagasse yield; Genotype; Silage quality; Sweet sorghum